Magic, science, and religion in early modern Europe - Waddell, Mark A. (New approaches to the history of science and medicine, 2021)
"From the recovery of ancient ritual magic at the height of the Renaissance to the ignominious demise of alchemy at the dawn of the Enlightenment, Mark A. Waddell explores the rich and complex ways that premodern people made sense of their world. He describes a time when witches flew through the dark of night to feast on the flesh of unbaptized infants, magicians conversed with angels or struck pacts with demons, and astrologers cast the horoscopes of royalty. Ground-breaking discoveries changed the way that people understood the universe while, in laboratories and coffee houses, philosophers discussed how to reconcile the scientific method with the veneration of God. This engaging, illustrated new study introduces readers to the vibrant history behind the emergence of the modern world"--